Aufgaben
Wende auf die Aufgaben die dritte binomische Formel an.
Aufgabe 1:
(2x + 2y) · (2x - 2y)
Aufgabe 2:
(3x + 8y) · (3x - 8y)
Aufgabe 3:
(2x + 3y) · (2x - 3y)
Aufgabe 4:
(3x + 5y) · (3x - 5y)
Aufgabe 5:
(6x + 4y) · (6x - 4y)
Aufgabe 6:
(10x + 2y) · (10x - 2y)
Aufgabe 7:
(1x + 9y) · (1x - 9y)
Aufgabe 8:
(4x + 6y) · (4x - 6y)
Aufgabe 9:
(6x + 2y) · (6x - 2y)
Aufgabe 10:
(2x + 4y) · (2x - 4y)
Aufgabe 11:
(5x + 4y) · (5x - 4y)
Aufgabe 12:
(5x + 8y) · (5x - 8y)
Lösungen
Aufgabe 1:
(2x + 2y) · (2x - 2y) = 4x
2 - 4y
2
a = 2x | a2 = (2x)2 = 4x2 |
b = 2y | b2 = (2y)2 = 4y2 |
Aufgabe 2:
(3x + 8y) · (3x - 8y) = 9x
2 - 64y
2
a = 3x | a2 = (3x)2 = 9x2 |
b = 8y | b2 = (8y)2 = 64y2 |
Aufgabe 3:
(2x + 3y) · (2x - 3y) = 4x
2 - 9y
2
a = 2x | a2 = (2x)2 = 4x2 |
b = 3y | b2 = (3y)2 = 9y2 |
Aufgabe 4:
(3x + 5y) · (3x - 5y) = 9x
2 - 25y
2
a = 3x | a2 = (3x)2 = 9x2 |
b = 5y | b2 = (5y)2 = 25y2 |
Aufgabe 5:
(6x + 4y) · (6x - 4y) = 36x
2 - 16y
2
a = 6x | a2 = (6x)2 = 36x2 |
b = 4y | b2 = (4y)2 = 16y2 |
Aufgabe 6:
(10x + 2y) · (10x - 2y) = 100x
2 - 4y
2
a = 10x | a2 = (10x)2 = 100x2 |
b = 2y | b2 = (2y)2 = 4y2 |
Aufgabe 7:
(1x + 9y) · (1x - 9y) = 1x
2 - 81y
2
a = 1x | a2 = (1x)2 = 1x2 |
b = 9y | b2 = (9y)2 = 81y2 |
Aufgabe 8:
(4x + 6y) · (4x - 6y) = 16x
2 - 36y
2
a = 4x | a2 = (4x)2 = 16x2 |
b = 6y | b2 = (6y)2 = 36y2 |
Aufgabe 9:
(6x + 2y) · (6x - 2y) = 36x
2 - 4y
2
a = 6x | a2 = (6x)2 = 36x2 |
b = 2y | b2 = (2y)2 = 4y2 |
Aufgabe 10:
(2x + 4y) · (2x - 4y) = 4x
2 - 16y
2
a = 2x | a2 = (2x)2 = 4x2 |
b = 4y | b2 = (4y)2 = 16y2 |
Aufgabe 11:
(5x + 4y) · (5x - 4y) = 25x
2 - 16y
2
a = 5x | a2 = (5x)2 = 25x2 |
b = 4y | b2 = (4y)2 = 16y2 |
Aufgabe 12:
(5x + 8y) · (5x - 8y) = 25x
2 - 64y
2
a = 5x | a2 = (5x)2 = 25x2 |
b = 8y | b2 = (8y)2 = 64y2 |